Education and faith: Luther ideas, German immigration to Brazil and the community-organized schools (19th-20th centuries) - Ademir Valdir dos Santos (Perspectiva)
The research aims to analyze, based on the relations between German immigration, Lutheranism and the process of creation of schools, the historical incorporation of ideas on education of Luther and its influence in the south of Brazil, in a period between the second decade of century XIX and the first decades of the twentieth century. The methodology is characterized by documentary research with the use of sources referring to the creation of schools, discussed based on a bibliographic reference that includes Luther texts and studies that deal with the links between religion and schooling. The results highlight the importance attributed to the school by Luther, understanding him as a religious reformer of Education. They show that the creation of schools by groups of German Lutheran immigrants in the Brazilian South is justified by their foundation in Lutheran conceptions. The schools were created so that children and young people could have access to religious principles and overcome the difficulties of living in a cultural environment different from that of the regions of origin. These reasons were reinforced by the absence of primary schools maintained by the government, either in the Empire period or in the first decades of the Republic. It is concluded that community schools founded on the colonies meant responses to the divine call to act in human education in harmony with faith, being understood as a result of Lutheran inspiration.